2018
DOI: 10.11591/ijere.v7i3.14019
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Educational Outcomes of Students with Multiple Disabilities: Results from a National Study

Abstract: <p>Parents, siblings, and peers have an immeasurable effect on shaping children into who they become as individuals. Many factors, such as one’s relationships with these individuals, may have lasting effects on the educational and vocational outcomes of children who have multiple disabilities. The purpose of the present study is to investigate the relationships of children with multiple disabilities, as well as their perceptions regarding their educational experiences to determine the effects these facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…Not with standing these international commitment and progress in international level, universal and inclusive education of people with disabilities in Indonesia further to be accomplished. Moreover, research reported by [4] that the students with disabilities endorsed their interest to attend college higher than those without disabilities. As a result, interest over inclusive education in every level of education in Indonesia has been growing.…”
Section: Introductionmentioning
confidence: 99%
“…Not with standing these international commitment and progress in international level, universal and inclusive education of people with disabilities in Indonesia further to be accomplished. Moreover, research reported by [4] that the students with disabilities endorsed their interest to attend college higher than those without disabilities. As a result, interest over inclusive education in every level of education in Indonesia has been growing.…”
Section: Introductionmentioning
confidence: 99%